A Case Study Evaluating Economic Implications of Two Grazing Strategies for Cattle Ranches in Northwest Argentina - Quiroga, Raul Emiliano; Blanco, Lisandro Javier; Ferrando, Carlos Alberto (Elsevier, 2021)
In the Argentinean Chaco Arido region, cattle production based on cow–calf operations is the principal source of agricultural income, and rangeland is the main forage source for cattle. Traditional grazing strategy (TGS, high stocking rate and continuous grazing) is considered the main cause of current rangeland degradation. Research shows that rangeland and cattle production improvements are possible when using a conservative grazing strategy (CGS, moderate stocking rate and rest rotation grazing). The aim of this research was to compare the effects of TGS and CGS applications on economic results for a cattle ranch in the region. To achieve this objective we used an approach that included estimations of forage and cattle production, and economic results. The study period was 1972/73–1983/84. Results showed that during the study period forage production and herd size were almost doubled with CGS, but maintained with TGS. The difference in net income between CGS and TGS (in Argentinean pesos, $), increased linearly from negative (-$2.88 · ha-1) to positive ($4.48 · ha-1) in the first 4 yr, and then was maintained at positive values (averaging $4.48 · ha-1). Data suggest that CGS leads to higher productivity and better economic results than TGS in the medium and long terms.